Characteristics of Nutrients and Microbiological Dadih Puding as Food Supplementation for Children with Sars-Cov-2 Infection - Hafifatul A Rahmy; Susmiati Susmiati; Asrawati Asrawati; Nice Rachmawati; Finny Fitry Yani; Helmizar Helmizar (Faculty of Public Health, Andalas University, 2022)
The Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) that cause COVID-19 global pandemic is a devastating disease causing thousands of victims every day. Therefore, there must be a certain effort to reduce the risk of the disease progress, including improvement of individual immune system like the probiotic supplementation. Meanwhile, dadih is a dairy product obtained from fermented buffalo milk contains various nutrients for human body, especially probiotics that beneficial for reducing the risk of COVID-19 infection in children. The aim of the study was to determine the nutritional and microbiological content of dadih pudding as additional supplementation in children confirmed positive for COVID-19. The study design was True Experiment using Completely Randomized Design (CRD). It consisted of four formulas. They were F0 as the standard formula, then F1, F2, and F3 as the treatment formula by adding dadih 50, 60, 70, and 80 grams, respectively. This study was initiated with the analysis of biochemical nutritional valueÂ at a laboratory in Padang Research Center and Industry Standardization. Besides, it also determined the number of total Acid Lactic Bacterial quantification which was analyzed at microbiology laboratory, Agricultured Technology Faculty, UniversitasÂ Andalas. Nutrients and lactic acid bacteria in dadih pudding are potential as food supplementation, especially for children with COVID-19 infection. It is strongly recommended to give probiotic dadih to children in order to counter oxidative stress and inflammation, and the setting of COVID-19.Â